1980
DOI: 10.1037/0278-7393.6.5.516
|View full text |Cite
|
Sign up to set email alerts
|

Reference points in spatial cognition.

Abstract: The present research investigates the hypothesis that cognitive representations of large scale space contain elements that may be termed reference points, and that these points are used to define the position of adjacent places. The nature and function of reference points is explored in five experiments. Experiments 1 and 2 consist of tasks during which subjects judged the distance between known locations. The subjective distance between reference points and nonreference points was found to be asymmetrical, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
135
1
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(154 citation statements)
references
References 17 publications
16
135
1
2
Order By: Relevance
“…Finally, it has been shown that segmentation affects time-duration estimation (Poynter, 1983;Zakay, Tsal, Moses, & Shahar, 1994). This result directly mirrors the effects of turning in the present study, and the explanation proposed for this effect on time estimation (Poynter, 1983) echoes the explanation provided just a few years earlier by Sadalla, Burroughs, and Staplin (1980) to explain turning effects.…”
Section: Discussionsupporting
confidence: 72%
“…Finally, it has been shown that segmentation affects time-duration estimation (Poynter, 1983;Zakay, Tsal, Moses, & Shahar, 1994). This result directly mirrors the effects of turning in the present study, and the explanation proposed for this effect on time estimation (Poynter, 1983) echoes the explanation provided just a few years earlier by Sadalla, Burroughs, and Staplin (1980) to explain turning effects.…”
Section: Discussionsupporting
confidence: 72%
“…We hypothesize that these differences are dependent upon spatial knowledge gained from body reference points. Only if body reference points provide salient spatial information by acting as organizing loci for other targets (Allen, Siegel, & Rosinski, 1978;Sadalla, Burroughs, & Staplin, 1980) is localization accomplished as proficiently with the abstracted spatial location code as with learned proprioceptive cues.…”
Section: Discussionmentioning
confidence: 99%
“…As stated earlier, the spatiallocation code has been hypothesized to be represented in memory as a point within a three-dimensional reference system (MacNeilage, 1970;Russell, 1976). And, since reference points are thought to be an integral component of spatial reference systems (Hart & Moore, 1973;Pick, Yonas, & Rieser, 1979;Sadalla, Burroughs, & Staplin, 1980), it is reasonable to assume that their availability will directly influence the development of the spatial location code. More specifically, the knowledge derived from spatial reference points may be necessary to construct a spatial location code that can sustain accurate orienting performance, and when such knowledge is absent, a less precise spatial location code will develop, resulting in an associated decrement in orienting performance.…”
mentioning
confidence: 99%
“…Despite the importance of linking objects with locations, research on memory for location has traditionally focused on how children and adults exploit spatial sources of information to remember locations. For example, many studies have examined how children and adults use boundaries and landmarks to remember locations (e.g., Acredolo & Evans, 1980;Holyoak & Mah, 1982;Kosslyn, Pick, & Fariello, 1974;McNamara, 1986;McNamara & Diwadkar, 1997;Newcombe & Liben, 1982;Sadalla, Burroughs, & Staplin, 1980). Very little is known about how people use nonspatial sources of information to remember the locations of objects.…”
mentioning
confidence: 99%